Gallic Acid Attenuates Angiotensin II-Induced Hypertension and Vascular Dysfunction by Inhibiting the Degradation of Endothelial Nitric Oxide Synthase - Yan, Xiao; Zhang, Qi-Yu; Zhang, Yun-Long; Han, Xiao; Guo, Shu-Bin; Li, Hui-Hua (Frontiers in Pharmacology, 2020)
Hypertension is a major cause of heart attack and stroke. Our recent study revealed that gallic acid (GA) exerts protective effects on pressure overload-induced cardiac hypertrophy and dysfunction. However, the role of GA in angiotensin II (Ang II)-induced hypertension and vascular remodeling remains unknown. C57BL/6J mice were subjected to saline and Ang II infusion. Systolic blood pressure was measured using a tail-cuff system. Vascular remodeling and oxidative stress were examined by histopathological staining. Vasodilatory function was evaluated in the aortic ring. Our findings revealed that GA administration significantly ameliorated Ang II-induced hypertension, vascular inflammation, and fibrosis. GA also abolished vascular endothelial dysfunction and oxidative stress in Ang II-infused aortas. Mechanistically, GA treatment attenuated Ang II-induced upregulation of the immunoproteasome catalytic subunits β2i and β5i leading to reduction of the trypsin-like and chymotrypsin-like activity of the proteasome, which suppressed degradation of endothelial nitric oxide synthase (eNOS) and reduction of nitric oxide (NO) levels. Furthermore, blocking eNOS activity by using a specific inhibitor (L-NG-nitroarginine methyl ester) markedly abolished the GA-mediated beneficial effect. This study identifies GA as a novel immunoproteasome inhibitor that may be a potential therapeutic agent for hypertension and vascular dysfunction.